2015
DOI: 10.1088/0026-1394/52/4/514
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for the atomic clock error in case of jumps

Abstract: We extend the mathematical model based on stochastic differential equations describing the error gained by an atomic clock to the cases of anomalous behavior including jumps and an increase of instability. We prove an exact iterative solution that can be useful for clock simulation, prediction, and interpretation, as well as for the understanding of the impact of clock error in the overall system in which clocks may be inserted as, for example, the Global Satellite Navigation Systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…where A is the amplitude, ] 0 is the central frequency of the oscillation, and φ(t) represents the random fluctuation in phase. e phase variations φ(t) is given as a summation of seven terms [35,36]:…”
Section: The Oscillator Modelmentioning
confidence: 99%
“…where A is the amplitude, ] 0 is the central frequency of the oscillation, and φ(t) represents the random fluctuation in phase. e phase variations φ(t) is given as a summation of seven terms [35,36]:…”
Section: The Oscillator Modelmentioning
confidence: 99%
“…Due to influences of intrinsic physical characteristics and outside environments, the SCB series will show non-stable characteristics (Heo et al, 2010). In addition, the on board atomic clocks are generally caesium or rubidium atomic clocks, and the frequency drift over an extended period of time is usually nonlinear (Galleani et al, 2003; Zucca and Tavella, 2015). The factors above will influence stability and accuracy of satellite clocks, and lead to clock offset.…”
Section: Fusion-based Scb Prediction Methodsmentioning
confidence: 99%
“…The initial ambiguity of phase measurement is set to an integer number of cycle constant for each continuous arc, and cycle slips are also introduced at some epochs for certain satellites. The satellite clock offsets are obtained from CODE precise clock products, and the receiver clock offsets are simulated by stochastic differential equations (SDEs) [41], which are described in the next subsection. Moreover, some errors, such as the ocean tide loading displacement, PCOs, and PCVs, need to be included in the observation errors to ensure that the simulated observation data are as close to real data as possible.…”
Section: A Simulation Of Gnss Observations Connected With Ground Stamentioning
confidence: 99%
“…These random noises vary according to the type of clock. Previous studies have reported that WFM and RWFM are the predominant noises in high-precise atomic clocks [41], [44]. Accordingly, the mathematical model of the clock offset can be formulated as [41]:…”
Section: B Mathematical Model Of Clock Offsetmentioning
confidence: 99%